HPTLC Analysis of Aragwadhadi Kashaya and its Ingredients - Sanitha U M; R.Rajam (International Journal of Ayurveda and Pharma Research, 2024)
Decoctions, are basically the extraction of medicines into water by means of boiling. In Ayurveda it is known by the name ‘kwatha’, ‘kashaya’,’sritha’ and ‘niryooha’. The term kwatha is derived from word ‘kwathana’ which means boiling. Aragwadhadhi kashaya is mentioned in Sharngadhara Samhitha, ingredients of which are Aragwadha, Kanamoola, Tiktha, Mustha and Abhaya. All the ingredients were checked for its identity, purity and strength and only those satisfying the API parameters were taken for the study. Kashaya was prepared as per classical method mentioned in Sharngadhara Samhitha. The prepared kashaya was lyophilised and further this extract was used for analysis. The extract of decoction and extracts of individual ingredients were analysed HPTLC was done with two different concentrations of kashaya extract and extract of five individual ingredients in a single Merck, HPTLC Silica gel 60 F254 plate. Quantification was not done in this study, but the results provided valuable information on the presence of various compounds in the decoction. Further research could focus on quantifying these compounds to better understand their concentrations and potential effects. Rf values obtained from two different concentrations of kashaya extract were not exactly similar. There were very few identical Rf values in individual ingredients and kashaya extract.